Fundamentals of momentum, heat and mass transfer - Wicks, Charles E.; Wilson, Robert E.; Rorrer, Gregory L. (John Wiley, 2007)
Introduction to momentum transfer - Fluid statics - Description of a fluid in motion - Conservation of mass: control-volume approach - Newton's second law of motion: control-volume approach - Conservation of energy: control-volume approach - Shear stress in laminar flow - Analysis of a differential fluid element in laminar fow - Differential equations of fluid flow - Inviscid fluid flow - Dimensional analysis and similitude - Viscous flow - Flow in closed conduits - Fluid machinery - Fundamentals of heat transfer - Differential equations of heat transfer - Steady-state conduction - Unsteady-state conduction - Convective heat transfer - Convective heat-transfer correlations - Boiling and condensaton - Heat-transfer equipment - Radiation heat transfer - Fundamental of mass transfer - Differential equations of mass transfer - Steady-state molecular diffusion - Unsteady-state molecular diffusion - Convective mass transfer - Convective mass transfer between phses - Convective mass-transfer correlatons - Mass-transfer equipment - Appendices.